The detection of occult metastatic disease in patients with cutaneous melanoma - Hanekom Gideon S (Division of Immunology, 2018)
The ability to identify melanoma patients with progressive disease is central to efficient management. The challenge therefore, is to develop prognostic markers and techniques which will allow the identification of those patients whom, at the time of primary tumor diagnosis, already have micrometastases (occult or clinically undetectable metastases). The use of the reverse transcription-PCR (RT-PCR) technique for the detection of circulating melanoma cells (CMCs) is potentially a powerful tool for identifying those patients at risk for developing metastases. The first aim of this study was to develop a more sensitive, reproducible, cost effective and clinically applicable assay and to eliminate the problem of false positives. A combined RT-PCR assay for tyrosinase mRNA, a marker specific for melanoma cells, was developed and tested. It was shown that the assay can reproducibly detect a single, viable melanoma cell in 10-15 ml of peripheral blood. Furthermore, a simple but effective procedure was developed to prevent carryover contamination. It was found that the chance of obtaining normal melanocyte contamination with the needle prick during blood sampling was only 2% and that illegitimate transcription does not contribute to sporadic false positives. The second aim of this study was to determine whether the early detection of CMCs is of any clinical value to monitor melanoma progression. Peripheral blood samples from 143 patients with primary melanoma (PM) were analysed by RT-PCR for the presence of tyrosinase mRNA. Seven percent (10/143) of the patients with PM had detectable CMCs. The percentage of PCR-positive patients was higher for stage II patients (9.0%) compared to stage I (5.3%) but the difference was not significant. A significantly higher percentage (P < 0.05) PCR-positive patients were found to have tumors greater than 1.5 mm thick and with ulceration present. Although this finding supports the notion that tumor thickness and ulceration are the two most significant prognostic factors, it was not possible at this stage, to link this directly to a poor prognosis since the majority of the PCR-positive patients have not yet (within four years) developed metastatic disease. However, the data does indicate that cells from tumors greater than 1.5 mm thick and with ulceration have a greater propensity to enter the circulation but that these cells do not necessarily have the ability to establish metastases. The results suggest that the detection rate of 9% for patients with stage II disease is much lower than would be expected, since 23.9% (16/67) of the stage II patients subsequently developed metastases. Of these 16 patients, only one was PCR-positive, one week before the metastases became clinically evident. Thus, the current technique fails to predict the likelihood of developing metastatic disease (P = 0.3485). The other nine PCR-positive patients had not yet developed metastases after a median follow-up period of four years. It is concluded that the current technique for the detection of CMCs is of limited clinical value to predict the likelihood of metastasis in patients with PM. It is suggested that other anatomic compartments, such as sentinel lymph nodes, should be explored for the identification of patients at risk for developing metastases. The third aim of this study was to determine whether high or low plasma levels and/or activity of plasminogen activator inhibitor type 1 (PAI1) correlate with the presence of metastatic disease in patients with melanoma. PAI1 is considered to be the main regulator of fibrinolytic activity in blood and has been identified as a key enzyme in the metastasis and vascularization of solid tumors. A unique enzyme-linked immunosorbant assay was developed to measure both the total amount of PAI1 in plasma as well as the active fraction of the inhibitor. This novel assay was then used to analyse and compare the plasmatic PAI1 levels and activity of a group of patients with advanced melanoma (AM) with a group of patients with primary disease and a control population. There was no statistical difference in the total plasmatic PAI1 levels between the controls and patients with PM and AM (P = 0.6199). In contrast, there was a significant difference in the active fraction of PAI1 between the controls and patients with PM or AM (P = 0.0076). A value of less than 44% active PAI1 was shown to be clinically meaningful by linear discriminant analysis. This means that a melanoma patient with a plasmatic PAI1 activity value less than 44% will have a 50% chance of harbouring metastases. Of the patients with PM, 19% had PAI1 activity values less than 44%, which strongly supports further investigations to determine whether plasmatic PAI1 activity levels might be predictive of metastatic disease. The false positive rate was 2.6%. It is speculated that this reduction in the active fraction of PAI1 for patients with AM might be attributed to tumor-derived tissue plasminogen activator and/or other melanoma-derived proteases or factors. The last section of this study describes several monoclonal antibodies (Mabs) that were developed against PAI1 in order to obtain useful reagents to study the regulatory functions of PAI1 in the metastasis and vascularization of solid tumors. The baculovirus expression system was used to express human PAI1 in insect cells and the crude infected cell population was used as the immunogen in mice. This approach was followed since the Escherichia coli-derived recombinant molecule elicited a poor immune response. A unique panel of anti-PAI1 Mabs was developed that were characterized with regard to their use for immunoblotting, immunofluorescence and immunocytochemistry. One of these antibodies blocked the binding of PAI1 to vitronectin and inhibited the activity of the inhibitor. Finally, two of these Mabs turned out to be extremely valuable and were used to develop a novel microtiter plate assay for measuring the active fraction of PAI1 in biological fluids by making use of Mabs against different epitopes of PAI1.